The yachting rule of art - Ansaloni,Giuditta Margherita Maria (2021)
Abstract Art and architecture have been unbreakably linked together for centuries, and the question that spontaneously arises is why it cannot be the same for art and yacht design. The field in which the research is carried out is placed at the crossroads between art and architecture, of which yacht design can be considered a category. There is a lack of references to the artistic field in the yachting sector in literature, so the parallelism between architecture and “floating” architecture is performed: the ships are the emblem of closure, and the stylistic evolution has begun bearing fruit in recent years. The paper aims to outline the current state of the art of the relationship between art and yachting. The first part analyses the relationship between art and architecture, while the second part discusses art concerning naval design: here, the case studies analysis highlights how art onboard is still considered an accessory rather than a backbone of the project.